Simulation-based Training in Ectopic Pregnancy and Salpingostomy - Sabatina, Isabella A (Cureus, 2019)
Objective Ectopic pregnancy leads to approximately 3% of deaths in pregnancy. Surgical management is indicated when patients are hemodynamically unstable or have signs of a ruptured ectopic pregnancy. Salpingectomy is more commonly performed, but salpingostomy is preferred in a patient with prior salpingectomy with a desire for future pregnancy. Due to the lack of exposure, salpingostomy is not frequently performed and most residents do not feel adequately trained. Our goal was to provide a hands-on simulation about ectopic pregnancy and salpingostomy in hopes that the simulation will improve the resident’s confidence and knowledge in recognizing an ectopic pregnancy, identifying an appropriate candidate for surgical management, and performing a salpingostomy. Methods The educational initiative was aimed towards postgraduate year (PGY) 1-4 OB/GYN residents (n=11). Knowledge and confidence questionnaires were given to participants prior to and post-simulation. A gynecologic mannequin was modified by taking the existing pelvic organs and creating a tubal pregnancy. In the first part of the simulation, a hemodynamically unstable patient presented with lab and imaging findings consistent with an ectopic pregnancy. Once recognized and the decision made for surgical intervention, participants were transferred to a simulated operating room where they performed salpingostomy or salpingectomy on the mannequin. The simulation was followed by a debriefing session to discuss the actions and thought processes of participants, provide reflection, and incorporate improvement opportunities for future cases. Finally, participants engaged in a didactic lecture where they were educated about the incidence, presentation, and management of tubal ectopic pregnancy. Results Analysis of the knowledge questionnaires showed the median score pre- and post-intervention was 9 and 12, respectively, with a median change of 3 (p=0.001). The median confidence value pre- and post-intervention were 28 and 42, respectively, with a median value change of 12 (p<0.001). Conclusion Our intervention improved residents' confidence and knowledge in recognizing an ectopic pregnancy, identifying an appropriate candidate for surgical management, and performing a salpingostomy.